Improvement of a PCR-based method for the detection of Opisthorchis viverrini eggs in human stool samples by targeting internal transcribed spacer-2 (ITS-2), cytochrome oxidase subunit 1 (cox1), and cytochrome b (cyb) - Pumpa, Supaporn (J Parasit Dis, 2021)
Opisthorchis viverrini infection causes various complications in patients, ranging from asymptomatic to severe chronic disease including cholangiocarcinoma (CCA). O. viverrini is endemic in Southeast Asia and acting as a risk for CCA. Early diagnosis of O. viverrini infection can reduce the number of CCA cases. The routine diagnosis for opisthorchiasis is direct wet smear, sometimes coupled with concentration techniques, which has limitations when investigating light infection or if done by laboratorians with lack of experiences. PCR-based methods have been established for the detection of O. viverrini egg DNA from stool samples, but have never fully succeeded for light infections when compared to wet smear concentration techniques. This study aims to improve the PCR-based method for detection of O. viverrini eggs in stool samples by targeting the genes ITS-2, cox1, and cyb. The results reveal higher sensitivity than conventional concentration techniques, with all newly designed primers. ITS-2 has an overall sensitivity of 76.9% with 66.7% in the samples with < 50 EPG, while cox1 has shown 96.2% overall sensitivity and 94.1% in the same EPG intervals. Interestingly, the new pointing target, cyb, has shown 100% sensitivity in all egg intervals in this study, particularly for light infections (EPG less than 100). No cross-reactivity was found in Taenia spp., Trichuris trichiura, Ascaris lumbricoides, Capillaria philippinensis, and hookworm. The procedure is convenient, with shorter steps compared to previous reports, and it appears appropriate for use in the diagnosis of light infection with O. viverrini. These three genes are good candidates for use in PCR-based detection of the parasite eggs. Further testing with a larger cluster of samples is however necessary.